Flame-retardant in-situ polymerization gel electrolyte battery and preparation method thereof

By using in-situ polymerization technology mixed by liquid electrolyte, polymerized monomer, crosslinking agent, flame retardant and initiator in lithium metal batteries, a gel electrolyte with flame retardant effect is formed, and the prior art is solved. The problems of flammable, low ionic conductivity and poor interface compatibility improve the stability and performance of the battery.

CN119153771APending Publication Date: 2024-12-17SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 6 Cited by

Patent Information

Application Number
CN202411079344.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing semi-solid gel electrolytes have problems such as flammability, low ionic conductivity and poor interfacial compatibility, which hinders the further development of lithium metal batteries.

Method used

The flame-retardant in-situ polymerization gel electrolyte formed by mixing liquid electrolyte, polymerized monomer, crosslinking agent, flame retardant and initiator, and the reaction is initiated by heat-induced by the polymerized monomer and the crosslinking agent. The space network structure is filled with liquid electrolyte and flame retardant, improving the mechanical properties and ion conductivity of the electrolyte.

Benefits of technology

It enhances the interface stability and cyclic stability between the electrolyte and the positive/negative electrode, reduces the battery impedance, improves the rapid transmission of lithium ions and the safety of the battery, and achieves flame retardant effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153771A_ABST
    Figure CN119153771A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium metal batteries, in particular to a flame-retardant in-situ polymerization gel electrolyte battery and a preparation method thereof.The flame-retardant in-situ polymerization gel electrolyte battery comprises a positive plate, a negative plate, a diaphragm and gel electrolyte; the gel electrolyte is mainly formed by mixing a liquid electrolyte, a polymeric monomer, a cross-linking agent, a flame retardant and an initiator and then performing in-situ polymerization. A polymeric monomer and a cross-linking agent are subjected to a thermally-initiated in-situ free radical polymerization reaction, a spatial net-shaped structure is formed through a cross-linked molecular chain, and the polymer is filled with a liquid electrolyte and a flame retardant, so that the gel electrolyte with a flame-retardant effect is obtained and is applied to a lithium metal battery; and the interface stability and cycle stability between the electrolyte and the positive / negative electrode can be enhanced. Meanwhile, the mechanical property of the gel electrolyte can be adjusted and improved by utilizing the polymeric monomer, so that a solid-solid contact interface in the battery can be improved; moreover, through component optimization, the ionic conductivity of the gel electrolyte can be improved, and rapid transmission of lithium ions is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium metal batteries, and in particular to a flame retardant in-situ polymerized gel electrolyte battery and a preparation method thereof. Background Art

[0002] With the increasing popularity of portable electronic devices and the rapid development of electric vehicles, energy storage devices represented by lithium batteries have been rapidly developed and widely used. Among them, lithium batteries with metallic lithium as the negative electrode are considered to be the most promising negative electrode materials in the next generation of high energy density battery systems due to their high theoretical capacity and low redox potential. However, current commercial liquid electrolytes face safety hazards such as leakage and combustion, as well as poor performance problems such as short battery cycle life. These challenges have hindered the further development of lithium metal batteries, and the use of solid electrolytes instead of liquid electrolytes is expected to fundamentally solve safety problems.

[0003] As polymer solid electrolytes for lithium-ion batteries, in order to improve the ionic conductivity of polymer electrolytes, polymers with excellent affinity and good chemical stability with liquid electrolytes are usually selected as the matrix material of gel polymer electrolytes. Semi-solid batteries can effectively reduce the amount of liquid electrolyte used in the battery, while increasing the energy density of the battery, and simultaneously reducing the potential safety hazards caused by the liquid electrolyte. In addition, semi-solid gel electrolytes can effectively inhibit the changes in the negative electrode structure and the growth of metal dendrites to a certain extent, and can greatly improve the safety of the battery while increasing the specific energy. However, existing semi-solid gel electrolytes often have shortcomings such as high battery impedance after combination and large performance loss. Therefore, the current strategy is not enough to achieve a flame-retardant liquid electrolyte or gel electrolyte with both high ionic conductivity and high interface compatibility.

[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a flame retardant in-situ polymerized gel electrolyte battery and a preparation method thereof, aiming to solve the problems of flammability, low ionic conductivity and poor interface compatibility of the existing gel electrolyte.

[0006] The technical solution of the present invention is as follows:

[0007] A flame retardant in-situ polymerized gel electrolyte battery comprises a positive electrode sheet, a negative electrode sheet, a separator and a gel electrolyte, wherein the gel electrolyte is mainly formed by mixing a liquid electrolyte, a polymerizable monomer, a crosslinking agent, a flame retardant and an initiator and then polymerizing them in-situ.

[0008] The flame retardant in-situ polymerized gel electrolyte battery, wherein the polymerized monomers are composed of carbonate-containing polymerized monomers and fluorine-containing polymerized monomers.

[0009] The flame-retardant in-situ polymerized gel electrolyte battery, wherein the carbonate-based polymerized monomer is selected from one or more of vinylene carbonate, pentaerythritol tetraacrylate, ethyl acrylate, butyl acrylate, allyl acetoacetate, hydroxyethyl acrylate, methyl methacrylate, ethyl cyanoacrylate, hydroxypropyl methacrylate, poly(ethylene glycol) methyl ether methacrylate; and / or the fluorine-containing polymerized monomer is selected from one or more of octafluoro-1,6-hexanediol diacrylate, trifluoroethyl methacrylate, hexafluorobutyl acrylate, perfluorooctyl ethyl acrylate, hexafluoroisopropyl acrylate, octafluoropentyl acrylate, tetrafluoropropyl methacrylate.

[0010] The flame retardant in-situ polymerized gel electrolyte battery, wherein the content of the polymerized monomer is 10wt%-50wt% of the total amount of the polymerized monomer and the liquid electrolyte, the content of the cross-linking agent is 5wt%-20wt% of the polymerized monomer, the content of the flame retardant is 1wt%-10wt% of the polymerized monomer, and the content of the initiator is 0.1wt%-1wt% of the polymerized monomer.

[0011] The flame-retardant in-situ polymerized gel electrolyte battery, wherein the liquid electrolyte comprises one of a carbonate electrolyte and an ether electrolyte; the liquid electrolyte contains a lithium salt; the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium difluorobis(oxalatophosphate).

[0012] The flame-retardant in-situ polymerized gel electrolyte battery, wherein the cross-linking agent is selected from one or more of polyethylene glycol dimethacrylate having an ether oxygen bond, polybutylene glycol diacrylate having an ether oxygen bond, ethylene glycol diacrylate having an ether oxygen bond, and polypropylene glycol glycidyl ether having an ether oxygen bond.

[0013] The flame retardant in-situ polymerized gel electrolyte battery, wherein the flame retardant is selected from one or more of phosphorus-based 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(2,3-dibromopropyl) phosphate, tris(monochloropropyl) phosphate, triphenyl phosphate, resorcinol bis(diphenyl phosphate), and triethyl phosphate.

[0014] In the flame-retardant in-situ polymerized gel electrolyte battery, the initiator is selected from one or more of benzoyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, and azobismethylvaleronitrile.

[0015] A method for preparing a flame retardant in-situ polymerized gel electrolyte battery comprises the following steps:

[0016] Mixing a liquid electrolyte, a polymerizable monomer, a cross-linking agent, a flame retardant and an initiator to obtain an electrolyte precursor reaction solution;

[0017] The positive electrode sheet, the separator and the negative electrode sheet are assembled into a battery pack and injected with the electrolyte precursor reaction solution, and a flame retardant in-situ polymerized gel electrolyte battery is obtained through a gel reaction.

[0018] The method for preparing the flame-retardant in-situ polymerized gel electrolyte battery comprises the following steps: the temperature of the gel reaction is 50° C.-60° C.; and the time of the gel reaction is 10 h-24 h.

[0019] Beneficial effects: The present invention provides a flame-retardant in-situ polymerized gel electrolyte battery and a preparation method thereof. The flame-retardant in-situ polymerized gel electrolyte battery comprises a positive electrode sheet, a negative electrode sheet, a separator and a gel electrolyte. The gel electrolyte is mainly formed by in-situ polymerization after a liquid electrolyte, a polymerized monomer, a cross-linking agent, a flame retardant and an initiator are mixed. The present invention conducts a heat-induced in-situ free radical polymerization reaction on the polymerized monomer and the cross-linking agent, forms a spatial network structure by cross-linking molecular chains, and the polymer is filled with liquid electrolyte and flame retardant, so as to obtain a gel electrolyte with flame retardant effect. When applied to lithium metal batteries, the interface stability and cycle stability between the electrolyte and the positive / negative electrodes can be enhanced. At the same time, the mechanical properties of the gel electrolyte can be adjusted and improved by using the polymerized monomer, which is beneficial to improving the solid-solid contact interface in the battery; and, by optimizing the components, the ionic conductivity of the gel electrolyte can be improved, which is conducive to the rapid transmission of lithium ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a schematic cross-sectional view of the flame-retardant in-situ polymerized gel electrolyte battery in Example 1;

[0021] Figure 2 This is a physical picture of the electrolyte precursor reaction solution after heating and polymerization in Example 1;

[0022] Figure 3 This is a comparison chart of the combustion experiments of the flame-retardant in-situ polymerized gel electrolyte and the liquid electrolyte prepared in Example 1;

[0023] Figure 4 This is a comparison chart of the room temperature ionic conductivity of the flame retardant in-situ polymerized gel electrolyte and the liquid electrolyte prepared in Example 1;

[0024] Figure 5 This is a comparison chart of the lithium symmetric battery cycle performance of the flame-retardant in-situ polymerized gel electrolyte and the liquid electrolyte prepared in Example 1;

[0025] Figure 6This is a comparison chart of the room temperature cycling performance of Li||LCO batteries assembled with the flame-retardant in-situ polymerized gel electrolyte prepared in Example 1 and a liquid electrolyte. DETAILED DESCRIPTION

[0026] The present invention provides a flame retardant in-situ polymerized gel electrolyte battery and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0027] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.

[0028] The invention provides a flame retardant in-situ polymerized gel electrolyte battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and a gel electrolyte, wherein the gel electrolyte is mainly formed by mixing a liquid electrolyte, a polymerizable monomer, a crosslinking agent, a flame retardant and an initiator and then polymerizing them in-situ.

[0029] In this embodiment, the gel electrolyte is loaded on the diaphragm, and the diaphragm loaded with the gel electrolyte is sandwiched between the positive electrode and the negative electrode to form a flame-retardant in-situ polymerized gel electrolyte battery. The present invention reduces the battery impedance and improves the battery cycle performance by improving the composition of the gel electrolyte; adding polymerized monomers to the liquid electrolyte can adjust and improve the mechanical properties of the gel electrolyte, which is beneficial to improving the solid-solid contact interface in the battery; and the present invention improves the ion conductivity of the gel electrolyte by optimizing the components, and the polymer formed by the in-situ polymerization of the polymerized monomers has excellent solubility for lithium salts and a wider electrochemical window, which is conducive to the rapid transmission of lithium ions; at the same time, the polymer can participate in regulating the migration of lithium ions, and the fluorinated part on the side chain reacts with the lithium metal anode to form LiF, inhibit the growth of lithium dendrites, and improve the stability of the lithium metal negative electrode. In addition, the cross-linking agent acts as a flexible cross-linking point, which helps the formation of the gel electrolyte and promotes the transmission of lithium ions.

[0030] Specifically, the present invention conducts a heat-induced in-situ free radical polymerization reaction of polymerized monomers and cross-linking agents, forms a spatial network structure by cross-linking molecular chains, and fills the polymer with liquid electrolyte and flame retardant to obtain a gel electrolyte with flame retardant effect, which can be applied to lithium metal batteries to enhance the interface stability and cycle stability between the electrolyte and the positive / negative electrodes. At the same time, the use of polymerized monomers can adjust and improve the mechanical properties of the gel electrolyte, which is beneficial to improve the solid-solid contact interface in the battery; and, by optimizing the components, the ion conductivity of the gel electrolyte can be improved, which is conducive to the rapid transmission of lithium ions.

[0031] In some embodiments, the polymerized monomers are composed of carbonate-containing polymerized monomers and fluorine-containing polymerized monomers. When carbonate-containing polymerized monomers and polymerized monomers containing strong electron-withdrawing groups of fluorine are combined, the mechanical properties of the gel electrolyte can be adjusted and improved, which is beneficial to improving the solid-solid contact interface in the battery.

[0032] Specifically, the present invention conducts a heat-induced in-situ free radical polymerization reaction of a carbonate-based polymer monomer and a fluorine-containing polymer monomer having an unsaturated carbon-carbon double bond with a cross-linking agent, forms a spatial network structure by cross-linking molecular chains, and fills the polymer with a liquid electrolyte to obtain a gel electrolyte with a flame retardant effect. When applied to lithium metal batteries, the interface stability between the electrolyte and the positive / negative electrode and the cycle stability can be enhanced.

[0033] In some embodiments, the polymer monomer is composed of a carbonate-containing polymer monomer and a fluorine-containing polymer monomer in a volume ratio of (4-1): (1-4). By copolymerizing the monomers in different ratios, the crystallinity of the polymer is reduced, the mechanical flexibility of the polymer is improved, and ion migration is promoted; wherein the polar group in the carbonate-based polymer monomer can promote the dissociation of lithium salts and improve the ionic conductivity of the polymer; and the introduction of a polymer monomer containing a strong electron-withdrawing group F element can further reduce the highest occupied molecular orbital (HOMO) energy level of the polymer and broaden the electrochemical stability window of the gel polymer electrolyte.

[0034] In a preferred embodiment, the volume ratio of the carbonate-containing polymerizable monomer to the fluorine-containing polymerizable monomer is 1:1, 4:1 or 1:4.

[0035] In some embodiments, the carbonate-containing polymer monomer is selected from but not limited to one or more of vinylene carbonate (VC), pentaerythritol tetraacrylate (PETEA), ethyl acrylate (EA), butyl acrylate (BA), allyl acetoacetate (AOA), hydroxyethyl acrylate (HEA), methyl methacrylate (MMA), ethyl cyanoacrylate (ECA), hydroxypropyl methacrylate (HPMA), and poly(ethylene glycol) methyl ether methacrylate (PEGMA). The carbonate-containing polymer monomer contains a strong polar carbonate group, a high dielectric constant, and can effectively reduce the interaction between anions and cations, reduce ion aggregation, increase the number of carriers, and enhance ion conductivity. In addition, the polyester polymer has a large number of electron-withdrawing groups (C=O), and its HOMO energy level is significantly lower than that of the polyether. At the same time, the carbonate-containing polymer monomer has excellent solubility for lithium salts and a wide electrochemical window, which is conducive to the rapid transmission of lithium ions.

[0036] In some embodiments, the fluorine-containing polymer monomer is selected from but not limited to one or more of octafluoro-1,6-hexanediol diacrylate (OFHDODA), trifluoroethyl methacrylate (TFEMA), hexafluorobutyl acrylate (HFBA), perfluorooctylethyl acrylate (PFA), hexafluoroisopropyl acrylate (HFIPA), octafluoropentyl acrylate (OFPA), and tetrafluoropropyl methacrylate (4FMA). The introduction of strong electron-withdrawing functional groups such as F elements into the above-mentioned polymer molecular chains can reduce the HOMO of the polymer electrolyte, so that the polymer has higher electrochemical oxidation stability. Furthermore, monomers containing strongly electron-withdrawing fluorine groups can participate in regulating the migration of lithium ions, and the fluorinated part on the side chain reacts with the lithium metal anode to form LiF, thereby inhibiting the growth of lithium dendrites.

[0037] In some embodiments, the content of the polymerized monomer is 10wt%-50wt% of the total amount of the polymerized monomer and the liquid electrolyte, the content of the cross-linking agent is 5wt%-20wt% of the polymerized monomer, the content of the flame retardant is 1wt%-10wt% of the polymerized monomer, and the content of the initiator is 0.1wt%-1wt% of the polymerized monomer. The crystallinity of the polymer is reduced by copolymerization, the mechanical flexibility of the polymer is improved, and ion migration is promoted. By adopting an appropriate content of the polymerized monomer, a high room temperature ionic conductivity is maintained while the electrolyte forms a gel state. If the amount of the polymerized monomer is too high, the internal resistance of the battery will increase, and the polarization of the battery will increase; if the amount of the polymerized monomer is too low, incomplete gelation will result. If the content of the cross-linking agent is too high, the pores of the molecular chain network formed after polymerization will be reduced, which is not conducive to the encapsulation of the electrolyte; if the amount of the cross-linking agent is too low, it is not conducive to the formation of a network of molecules in the electrolyte and cannot promote the formation of a gel state. If the amount of flame retardant is too much, it will cause the flame retardant to precipitate and introduce too many side reactions between the positive and negative electrodes; if the amount of flame retardant is too little, the flame retardant effect will be poor. Controlling the appropriate amount of initiator added can control the polymerization reaction to proceed at an appropriate reaction speed.

[0038] In some embodiments, the liquid electrolyte includes but is not limited to one of the commonly used commercial carbonate electrolytes and ether electrolytes; the liquid electrolyte contains a lithium salt; the lithium salt is selected from but is not limited to one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiCF3SO3), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiODFB), and lithium difluorobis(oxalatophosphate) (LiDFBP).

[0039] In some embodiments, the crosslinking agent is selected from but not limited to polyethylene glycol dimethacrylate (PEGDA) with ether oxygen bond, polybutylene glycol diacrylate (PBGDA) with ether oxygen bond, ethylene glycol diacrylate (DEGDA) with ether oxygen bond, polypropylene glycol glycidyl ether (PPGDGE) with ether oxygen bond. The molecular chain of the ether oxygen bond in the crosslinking agent has good flexibility, and as a flexible crosslinking point, it helps to form a gel electrolyte while promoting lithium ion transmission. In addition, it can provide good ionic conductivity, and is used in a gel electrolyte to help promote the encapsulation of the polymer to the liquid electrolyte, and has little negative impact on impedance and performance.

[0040] In some embodiments, the flame retardant is selected from, but not limited to, one or more of phosphorus-based 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), tris(2,3-dibromopropyl) phosphate (TBPP), tris(monochloropropyl) phosphate (TCPP), triphenyl phosphate (TPP), resorcinol bis(diphenyl phosphate) (RDP), and triethyl phosphate (TEP). The above phosphorus-based flame retardants are low in smoke, non-toxic, low in halogen, have long-lasting flame retardancy, and have high thermal and chemical stability.

[0041] In a preferred embodiment, the flame retardant is DOPO, which contains a PH bond in its structure and is extremely active to olefins, epoxy bonds and carbonyl groups. It can react to generate many derivatives, is halogen-free, smokeless, non-toxic, non-migrating, has long-lasting flame retardancy, and has high thermal and chemical stability.

[0042] In some embodiments, the initiator is selected from but not limited to one or more of benzoyl peroxide (BPO), azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), dimethyl azobisisobutyrate (AIBME), and azobismethylvaleronitrile (AMVN). Among them, the polymerization reaction rate initiated by AIBN is relatively high and the reaction is relatively violent. If too much is added and it contacts the electrode, there will be undesirable side reactions.

[0043] In some embodiments, the negative electrode sheet is but not limited to a silicon-carbon negative electrode, a lithium metal negative electrode or a lithium metal alloy negative electrode; the positive electrode material in the positive electrode sheet is but not limited to one of lithium cobalt oxide (LCO), lithium iron phosphate, lithium manganese oxide, and nickel cobalt manganese oxide.

[0044] In some embodiments, both the positive electrode sheet and the negative electrode sheet contain a conductive agent and a binder; the conductive agent includes but is not limited to one or more of carbon black (Super P), acetylene black, multi-walled carbon nanotubes, and single-walled carbon nanotubes; the binder includes one or more of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), sodium carboxymethyl cellulose (CMC), polyurethane (PU), styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), polyacrylic acid (PAA), and polyacrylonitrile (PAN).

[0045] In some embodiments, the separator includes one or more of a polyethylene separator (PE), a polypropylene separator (PP), a polyimide separator (PI), a para-aramid composite separator, and a cellulose separator.

[0046] In addition, the present invention also provides a method for preparing a flame retardant in-situ polymerized gel electrolyte battery, comprising the steps of:

[0047] Step S10: mixing a liquid electrolyte, a polymerizable monomer, a cross-linking agent, a flame retardant and an initiator to obtain an electrolyte precursor reaction solution;

[0048] Step S20: assembling the positive electrode sheet, the separator and the negative electrode sheet into a battery pack and injecting the electrolyte precursor reaction solution into the battery pack to obtain a flame-retardant in-situ polymerized gel electrolyte battery through a gel reaction.

[0049] In this embodiment, the polymerized monomer, cross-linking agent, flame retardant, and initiator are dispersed and mixed into the liquid electrolyte, stirred evenly to obtain an electrolyte precursor reaction solution, and then dripped onto the separator between the positive and negative electrodes of the battery and soaked when assembling the battery, and then heated at a temperature of not less than 50°C for at least 5 hours to polymerize the monomers therein in situ to obtain a flame retardant gel electrolyte. The present invention conducts a heat-induced in-situ free radical polymerization reaction of carbonate polymer monomers and fluorine-containing polymer monomers with a cross-linking agent, forms a spatial network structure by cross-linking molecular chains, and fills the polymer with liquid electrolyte to obtain a gel electrolyte with a flame retardant effect. In addition, the present invention improves the battery production process, utilizes in-situ polymerization with lower temperature and faster polymerization, and is produced, in-situ polymerized, and gelled in actual batteries, which is more suitable for actual battery production lines, and can effectively improve efficiency and reduce costs.

[0050] In some embodiments, the temperature of the gel reaction is 50°C-60°C, and the time of the gel reaction is 10h-24h. Some components in the electrolyte will be unstable under long-term high temperature and are prone to side reactions. It is necessary to control the polymerization temperature not to be too high and the reaction time not to be too long. Under this condition, the carbonate polymer monomer and the fluorine-containing polymer monomer with unsaturated carbon-carbon double bonds react with the cross-linking agent by thermally initiated in-situ free radical polymerization, and a spatial network structure is formed by cross-linking molecular chains. The polymer is filled with liquid electrolyte to obtain a gel electrolyte with a flame retardant effect.

[0051] Specifically, when preparing the flame-retardant in-situ polymerized gel electrolyte battery, the battery is injected and assembled, and after injection, it is allowed to stand and soak at a temperature of 20°C-40°C, preferably at 25°C-30°C for 10 hours; then the battery is placed at 50°C-60°C for gel reaction for 10 hours-24 hours, preferably at 60°C for 24 hours.

[0052] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.

[0053] Example 1

[0054] This embodiment provides a method for preparing a flame retardant in-situ polymerized gel electrolyte battery, wherein the structure of the flame retardant in-situ polymerized gel electrolyte battery is as follows: Figure 1 As shown, including positive electrode, negative electrode, separator and gel electrolyte, the process of preparing the battery is as follows:

[0055] 1) First, the slurry is mixed, wherein the positive electrode slurry ratio is LCO: Super P: PVDF = 80: 10: 10, all of which are weight percentage (wt%); the positive electrode slurry is coated on aluminum foil, dried, and cut into pole pieces with a diameter of 12 mm. The negative electrode uses lithium foil.

[0056] 2) The liquid electrolyte used in the electrolyte precursor reaction solution is a commercial electrolyte (Haopeng SEL003). VC (0.2 mL) and HFBA (0.2 mL) polymerization monomers in a volume ratio of 1:1, PBGDA cross-linking agent accounting for 10 wt% (0.0541 g) of the polymerization monomer, 1 wt% (0.0054 g) of TBPP flame retardant, and 0.3 wt% (0.0016 g) of BPO initiator were added to 4.8654 g of liquid electrolyte (90 wt%) and stirred evenly to obtain an electrolyte precursor reaction solution.

[0057] 3) The electrolyte precursor reaction solution is then injected during the battery assembly process.

[0058] 4) The battery was placed in a static soaking state at 25°C for 10 hours. After soaking, the battery was placed in a high temperature environment for gelling reaction at 60°C for 24 hours to obtain a gel electrolyte battery.

[0059] Example 2

[0060] The difference between this embodiment and embodiment 1 is that the components of the electrolyte precursor reaction solution are different, and the remaining steps are the same.

[0061] The preparation method of the electrolyte precursor reaction solution of the present embodiment includes: adding VC (0.2 mL) and HFBA (0.2 mL) polymerization monomers in a volume ratio of 1:1 and 10 wt% (0.0541 g) of PBGDA cross-linking agent accounting for 1 wt% (0.0054 g) of the polymerization monomer, 1 wt% (0.0054 g) of TBPP flame retardant, and 0.3 wt% (0.0016 g) of BPO initiator to 4.8654 g of liquid electrolyte (90 wt%), stirring evenly, and obtaining an electrolyte precursor reaction solution.

[0062] Example 3

[0063] The difference between this embodiment and embodiment 1 is that the components of the electrolyte precursor reaction solution are different, and the remaining steps are the same.

[0064] The preparation method of the electrolyte precursor reaction solution of the present embodiment includes: adding BA (0.1 mL) and TFEMA (0.4 mL) polymerization monomers in a volume ratio of 1:4 and PEGDA crosslinking agent accounting for 10 wt% (0.0562 g) of the polymerization monomers, 1 wt% (0.0055 g) of DOPO flame retardant, and 0.3 wt% (0.0017 g) of AIBN initiator to 5.0598 g of liquid electrolyte (90 wt%), stirring evenly, and obtaining an electrolyte precursor reaction solution.

[0065] Example 4

[0066] The difference between this embodiment and embodiment 1 is that the components of the electrolyte precursor reaction solution are different, and the remaining steps are the same.

[0067] The preparation method of the electrolyte precursor reaction solution of the present embodiment includes: adding MMA (0.4 mL) and HFIPA (0.1 mL) polymerization monomers in a volume ratio of 4:1 and PEGDA crosslinking agent accounting for 10 wt% (0.0512 g) of the polymerization monomers, 1 wt% (0.0051 g) of TCPP flame retardant, and 0.2 wt% (0.001 g) of AIBN initiator to 1.1937 g of liquid electrolyte (70 wt%), stirring evenly, and obtaining an electrolyte precursor reaction solution.

[0068] Example 5

[0069] The difference between this embodiment and embodiment 1 is that the components of the electrolyte precursor reaction solution are different, and the remaining steps are the same.

[0070] The preparation method of the electrolyte precursor reaction solution of the present embodiment includes: adding MMA (0.4 mL) and HFIPA (0.1 mL) polymerization monomers in a volume ratio of 4:1 and PEGDA crosslinking agent accounting for 10 wt% (0.0512 g) of the polymerization monomers, 5 wt% (0.0256 g) of TCPP flame retardant, and 0.2 wt% (0.001 g) of AIBN initiator to 1.1937 g of liquid electrolyte (70 wt%), stirring evenly, and obtaining an electrolyte precursor reaction solution.

[0071] Example 6

[0072] The difference between this embodiment and embodiment 1 is that the components of the electrolyte precursor reaction solution are different, and the remaining steps are the same.

[0073] The preparation method of the electrolyte precursor reaction solution of the present embodiment includes: adding PEGMA (0.2 mL) and HFIPA (0.2 mL) polymerization monomers in a volume ratio of 1:1 and PEGDA crosslinking agent accounting for 20 wt% (0.0958 g) of the polymerization monomers, 5 wt% (0.0239 g) of TCPP flame retardant, and 0.2 wt% (0.001 g) of AIBN initiator to 1.9152 g of liquid electrolyte (80 wt%), stirring evenly, and obtaining an electrolyte precursor reaction solution.

[0074] Example 7

[0075] The difference between this embodiment and embodiment 1 lies in the components of the electrolyte precursor reaction solution and the parameters of the gel reaction, and the remaining steps are the same.

[0076] The preparation method of the electrolyte precursor reaction solution of the present embodiment includes: adding PEGMA (0.1 mL) and 4FMA (0.4 mL) polymerization monomers in a volume ratio of 1:4 and PEGDA crosslinking agent accounting for 20 wt% (0.117 g) of the polymerization monomers, 1 wt% (0.0059 g) of RDP flame retardant, and 1 wt% (0.0059 g) of AIBN initiator to 2.34 g of liquid electrolyte (80 wt%), stirring evenly, and obtaining an electrolyte precursor reaction solution.

[0077] In this embodiment, the soaked battery is placed in a high temperature environment for gel reaction at a temperature of 50° C. for a reaction time of 12 h to obtain a gel electrolyte battery.

[0078] In order to more intuitively compare the components of the electrolyte precursor reaction solutions of Examples 1 to 7 and compare the performance of ionic conductivity and electrochemical stability window, the specific comparison is shown in Table 1:

[0079] Table 1

[0080]

[0081]

[0082] The flame retardant gel electrolyte prepared in Example 1 is characterized as follows:

[0083] Depend on Figure 1 The cross-sectional schematic diagram of the flame-retardant in-situ polymerization gel electrolyte battery shows that the in-situ polymerization method can improve the wetting of the gel electrolyte into the positive and negative electrode materials, thereby reducing the interface impedance between the electrolyte and the electrode.

[0084] Depend on Figure 2It can be seen that VC and HFBA monomers, PEGDA crosslinker and DOPO flame retardant can transform the liquid electrolyte into a gel electrolyte through an in situ polymerization process under the thermal initiation polymerization of AIBN.

[0085] Figure 3 The comparison diagram of the combustion experiment of the flame retardant in-situ polymerized gel electrolyte and the liquid electrolyte in Example 1 is shown in FIG. Figure 3 Combustion experiments show that liquid electrolytes are flammable and release a large amount of heat during continuous combustion; on the contrary, flame-retardant gel electrolytes are non-flammable when exposed to a fire source.

[0086] Depend on Figure 4 The room temperature ionic conductivity comparison chart shows that the ionic conductivity of the flame retardant gel electrolyte at room temperature is 0.67 mS cm -1 , close to the room temperature ionic conductivity of liquid electrolyte 0.89mS cm -1 , indicating that the flame-retardant gel electrolyte has excellent ionic conductivity.

[0087] The flame-retardant gel electrolyte prepared in Example 1 was matched with lithium to form a Li||Li symmetric battery with flame-retardant gel electrolyte, and a Li||Li symmetric battery with liquid electrolyte was used as a comparison. The two symmetric batteries were tested at 1 mA cm -2 and 1mAh cm -2 The long cycle test was carried out under the test conditions and the results were obtained. Figure 5 Cycling performance diagram. It can be seen that the Li||Li symmetric battery with flame-retardant gel electrolyte can stably cycle for 900h and maintain a low polarization voltage. On the contrary, the polarization voltage of the Li||Li symmetric battery with liquid electrolyte increases after cycling for 600h. The above results show that the introduction of flame-retardant gel electrolyte can inhibit the growth of lithium dendrites and stabilize the lithium metal anode.

[0088] The flame-retardant gel electrolyte prepared in Example 1 was matched with a lithium negative electrode and a lithium cobalt oxide positive electrode to assemble a Li||LCO battery with a flame-retardant gel electrolyte, and a Li||LCO battery with a liquid electrolyte was used as a comparison. The two batteries were subjected to a long cycle test under the test conditions of a current density of 1C and a voltage range of 2.75-4.55V, and the results were Figure 6 Cycling performance diagram. It can be seen that the Li||LCO battery with flame-retardant gel electrolyte can stably cycle 1000 times at 1C, and the capacity retention rate is 76.2%. In contrast, the cycling performance of the liquid electrolyte Li||LCO battery decays rapidly, and the capacity retention rate is only 44.6% after 1000 cycles. The above results show that the introduction of flame-retardant gel electrolyte helps to achieve long-cycle performance of lithium metal batteries at high voltage.

[0089] In summary, the present invention provides a flame-retardant in-situ polymerized gel electrolyte battery and a preparation method thereof. The flame-retardant in-situ polymerized gel electrolyte battery includes a positive electrode sheet, a negative electrode sheet, a separator and a gel electrolyte. The gel electrolyte is mainly formed by mixing a liquid electrolyte, a polymerized monomer, a cross-linking agent, a flame retardant and an initiator and then polymerizing them in situ. The present invention conducts a thermally initiated in-situ free radical polymerization reaction between the polymerized monomer and the cross-linking agent, forms a spatial network structure by cross-linking molecular chains, and the polymer is filled with liquid electrolyte and flame retardant, so as to obtain a gel electrolyte with flame retardant effect, which is applied to lithium metal batteries and can enhance the interface stability and cycle stability between the electrolyte and the positive / negative electrodes. At the same time, the mechanical properties of the gel electrolyte can be adjusted and improved by using the polymerized monomer, which is beneficial to improving the solid-solid contact interface in the battery; and, by optimizing the components, the ionic conductivity of the gel electrolyte can be improved, which is conducive to the rapid transmission of lithium ions.

[0090] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A flame retardant in-situ polymerized gel electrolyte battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and a gel electrolyte, characterized in that: The gel electrolyte is mainly formed by mixing a liquid electrolyte, a polymerizable monomer, a crosslinking agent, a flame retardant and an initiator and then subjecting the mixture to in-situ polymerization.

2. The flame retardant in-situ polymerized gel electrolyte battery according to claim 1, characterized in that: The polymerizable monomers consist of carbonate-containing polymerizable monomers and fluorine-containing polymerizable monomers.

3. The flame retardant in-situ polymerized gel electrolyte battery according to claim 2, characterized in that: The carbonate-containing polymerization monomer is selected from one or more of vinylene carbonate, pentaerythritol tetraacrylate, ethyl acrylate, butyl acrylate, allyl acetoacetate, hydroxyethyl acrylate, methyl methacrylate, ethyl cyanoacrylate, hydroxypropyl methacrylate, and poly(ethylene glycol) methyl ether methacrylate; and / or, the fluorine-containing polymerization monomer is selected from one or more of octafluoro-1,6-hexanediol diacrylate, trifluoroethyl methacrylate, hexafluorobutyl acrylate, perfluorooctyl ethyl acrylate, hexafluoroisopropyl acrylate, octafluoropentyl acrylate, and tetrafluoropropyl methacrylate.

4. The flame retardant in-situ polymerized gel electrolyte battery according to claim 1, characterized in that: The content of the polymerized monomer is 10wt%-50wt% of the total amount of the polymerized monomer and the liquid electrolyte, the content of the cross-linking agent is 5wt%-20wt% of the polymerized monomer, the content of the flame retardant is 1wt%-10wt% of the polymerized monomer, and the content of the initiator is 0.1wt%-1wt% of the polymerized monomer.

5. The flame retardant in-situ polymerized gel electrolyte battery according to claim 1, characterized in that: The liquid electrolyte comprises one of a carbonate electrolyte and an ether electrolyte; the liquid electrolyte contains a lithium salt; the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium difluorobis(oxalatophosphate).

6. The flame retardant in-situ polymerized gel electrolyte battery according to claim 1, characterized in that: The crosslinking agent is selected from one or more of polyethylene glycol dimethacrylate having an ether oxygen bond, polybutylene glycol diacrylate having an ether oxygen bond, ethylene glycol diacrylate having an ether oxygen bond, and polypropylene glycol glycidyl ether having an ether oxygen bond.

7. The flame retardant in-situ polymerized gel electrolyte battery according to claim 1, characterized in that: The flame retardant is selected from one or more of phosphorus-based 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, tris(2,3-dibromopropyl) phosphate, tris(monochloropropyl) phosphate, triphenyl phosphate, resorcinol bis(diphenyl phosphate), and triethyl phosphate.

8. The flame retardant in-situ polymerized gel electrolyte battery according to claim 1, characterized in that: The initiator is selected from one or more of benzoyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, and azobismethylvaleronitrile.

9. A method for preparing a flame retardant in-situ polymerized gel electrolyte battery according to any one of claims 1 to 8, characterized in that: Includes steps: Mixing a liquid electrolyte, a polymerizable monomer, a cross-linking agent, a flame retardant and an initiator to obtain an electrolyte precursor reaction solution; The positive electrode sheet, the separator and the negative electrode sheet are assembled into a battery pack and injected with the electrolyte precursor reaction solution, and a flame retardant in-situ polymerized gel electrolyte battery is obtained through a gel reaction.

10. The method for preparing a flame retardant in-situ polymerized gel electrolyte battery according to claim 9, characterized in that: The temperature of the gel reaction is 50° C.-60° C., and the time of the gel reaction is 10 h-24 h.

Citation Information

Cited By

  • Flame-retardant double-salt polymer solid electrolyte as well as preparation method and application thereof

    CN120376736A

  • Flame-retardant double-salt polymer solid-state electrolyte, preparation method and application thereof

    CN120376736B

  • Flame-retardant gel electrolyte, preparation method thereof and lithium ion battery containing electrolyte

    CN121507084A

  • Ion coordination type polymer solid electrolyte, battery as well as preparation method and application of ion coordination type polymer solid electrolyte

    CN122246262A

  • High-safety solid-state lithium battery based on ionic gel interface layer

    CN122393404A